Short-Term Outcome of Patients with Cirrhosis and Concurrent Portal Cavernoma Presenting with Acute Variceal Bleeding - Xuefeng Luo; Wanqin Wang; Xiaoli Fan; Ying Zhao; Xiaoze Wang; Jinlin Yang; Li Yang (Canadian Journal of Gastroenterology and Hepatology)
Background and Aim. The outcome of cirrhotic patients with main portal vein occlusion and portal cavernoma after the first episode of acute variceal bleeding (AVB) is unknown. We compared short-term outcomes after AVB in cirrhotic patients with and without portal cavernoma. Methods. Between January 2009 and September 2014, 28 patients with cirrhosis and portal cavernoma presenting with the first occurrence of AVB and 56 age-, sex-, and Child-Pugh score-matched cirrhotic patients without portal cavernoma were included. The primary endpoints were 5-day treatment failure and 6-week mortality. Results. The 5-day treatment failure rate was higher in the cavernoma group than in the control group (32.1% versus 12.5%; p=0.031). The 6-week mortality rate did not differ between the cavernoma and control group (25% versus 12.5%, p=0.137). Multivariable Cox proportional hazard regression analyses revealed that 5-day treatment failure (HR = 1.223, 95% CI = 1.082 to 1.384; p=0.001) independently predicted 6-week mortality. Conclusions. Cirrhotic patients with AVB and portal cavernoma have worse short-term prognosis than patients without portal cavernoma. The 5-day treatment failure was an independent risk factor for 6-week mortality in patients with cirrhosis and portal cavernoma.